Pengaruh Komitmen Karier Terhadap Kesuksesan Karier Dengan Tipe Karier Sebagai Variabel Moderasi Pada Pekerja Lepas Generasi Z - Naura Safinatunnajah; Aftina Nurul Husna (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Career commitment is an important psychological resource for career development, particularly in the context of freelance work, which is characterized by flexibility and a lack of formal career structures. As Generation Z's participation in the gig economy increases, empirical studies on the role of career commitment in freelancers' career success are still relatively limited, especially in Indonesia. This study aims to examine the influence of career commitment on career success and the role of career type as a moderating variable in Generation Z freelancers. This study used a quantitative approach with a cross-sectional survey design. Participants were 158 Generation Z freelancers aged 17–28 years old, using a stratified random sampling technique based on domicile. Career commitment was measured using the Career Commitment Scale, while career success was measured through subjective and objective indicators modified from previous research. Data were analyzed using linear regression and moderated regression analysis. The results showed that career commitment had a significant effect on career success. However, career type was not shown to moderate the relationship between career commitment and career success. These findings suggest that career commitment plays a significant role in enhancing the career success of Generation Z freelancers, regardless of their career type orientation. The theoretical implication of this research is the importance of considering the contemporary work context in understanding career dynamics, where the boundaries between linear and non-linear careers are becoming increasingly blurred. Practically, these findings emphasize the urgency of developing programs that focus on strengthening career commitment as a foundation for success for Generation Z freelancers.